2023
DOI: 10.1007/s40948-023-00561-z
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviors of coal surrounding horizontal wellbore during drilling process considering the effects of loading rate, pore pressure and temperature

Abstract: Coal is a kind of rock with the characteristics of soft structure, developed joints, cleats, cracks, and pores, resulting in that its mechanical behaviors are highly sensitive to stress, pore coalbed methane (CBM, gas) pressure and temperature. Thus, due to the variations in stress, pore pressure and temperature caused by the drilling operation, the coal surrounding wellbore can be easily damaged, which would cause serious wellbore instability problems. In this presented work, a stress path of loading axial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Tectonic coal is formed after long-term strong compression and shear deformation of primary coal. Coal mining practices have shown that most coal and gas outburst accidents in China and even globally are closely related to structural coal seams. , Compared to primary coal, structural coal exhibits characteristics of low strength and weak bonding, which play a crucial role in the occurrence and development of outburst . On the one hand, the low strength characteristics of structural coal reduce the outstanding mechanical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Tectonic coal is formed after long-term strong compression and shear deformation of primary coal. Coal mining practices have shown that most coal and gas outburst accidents in China and even globally are closely related to structural coal seams. , Compared to primary coal, structural coal exhibits characteristics of low strength and weak bonding, which play a crucial role in the occurrence and development of outburst . On the one hand, the low strength characteristics of structural coal reduce the outstanding mechanical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Coal reservoirs at these depths are typically characterized by low porosity, low permeability, and high heterogeneity, posing significant challenges and limitations for coal mining operations [4][5][6][7][8][9]. Therefore, the disposition of coal mine gas and the physical and mechanical properties of the coal rock mass have been a focus of research attention [10,11]. While coalbed methane can pose significant risks in coal mines, it also presents a promising opportunity as a clean, high-quality, and efficient energy source.…”
Section: Introductionmentioning
confidence: 99%